PENGGUNAAN PARTIKEL ILOKUSI NE DAN YO DALAM TUTURAN BAHASA JEPANG - Reny Wiyatasari (IZUMI, 2018)
(Title: Use of Illocutionary Particle in Japanese Language). The purpose of this study is to explain the use of illocutionary particles ne and yo, the pragmatic meaning generated from a speech and how the influence of the existence of each of these particles in a speech. Because ne and yo are pragmatic rather than semantic and this nature only occurs in verbal interactions, this article takes data from data sources, such as Japanese dramas and Japanese short stories. The data was collected using the observation method through recording and note-taking techniques, and then analyzed using contextual method.From the results of data analysis it was found that ne particles are used when a) request confirmation or ensure information, b) request or seek agreement, c) soften speech, and d) marking the feelings felt by the speaker. While yo particles are used when : a) confirming the question to get a response or reason, b) marking that information (statement) is something new for the listerner, c) emphasizing or affirming a matter/action intended by the speaker in his speech, d) marking speech means encouraging, e) marking utterances that contain expressions of the feeling of the speaker, and f) marking the urge to take action. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor